2000
DOI: 10.1063/1.372224
|View full text |Cite
|
Sign up to set email alerts
|

In situ ellipsometry growth characterization of dual ion beam deposited boron nitride thin films

Abstract: Pure hexagonal h, as well as mixed-phase cubic/hexagonal c/h boron nitride ͑BN͒ thin films were deposited onto ͓001͔ silicon substrates using the dual ion beam deposition technique. The BN thin films were grown under UHV conditions at different substrate temperatures and ion beam bombarding parameters. Thin-film growth was monitored using in situ spectroscopic ellipsometry at 44 wavelengths between 420 and 761 nm. The in situ ellipsometric ⌿ and ⌬ data were compared with two-layer growth model calculations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…5,6 Unfortunately, much like diamond films, the synthesis of crystalline BN films is still in its early stages of development. Furthermore, although polycrystalline BN films have been prepared by a variety of physical and chemical vapor deposition techniques, 7,8,9,10,11,12,13 the capability does not currently exist for depositing large area single-crystal or oriented films of BN. Such single-crystal films are required for many of the applications of interest.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Unfortunately, much like diamond films, the synthesis of crystalline BN films is still in its early stages of development. Furthermore, although polycrystalline BN films have been prepared by a variety of physical and chemical vapor deposition techniques, 7,8,9,10,11,12,13 the capability does not currently exist for depositing large area single-crystal or oriented films of BN. Such single-crystal films are required for many of the applications of interest.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] contain comparative reviews for these models. Most discussed models include the compressive stress model [7][8][9], preferential sputtering model [10,11], sub-plantation model [12][13][14][15], thermal spike model [16][17][18], and the nanoarches model [5]. It has been observed that, after the cubic phase nucleates on top of the h-BN basal planes, the energy of the ions could be lowered significantly while the growth of the cubic phase is maintained [19].…”
Section: Introductionmentioning
confidence: 99%
“…RTSE in the visible range ͑1.6-3.0 eV͒ has been applied recently to study BN film growth. 5 The poor optical contrast between hBN and cBN in this range, however, makes it difficult to distinguish the phase evolution from possible microstructural evolution ͑e.g., void fraction variations͒. Bulk cBN is isotropic with an index of refraction in the visible spectral range of nϳ2.1; hBN is uniaxial with values of the ordinary and extraordinary indices of n o ϳ2.17 and n e ϳ1.65, respectively.…”
mentioning
confidence: 99%